Electrospun Nanofibrous Materials as Stimuli‐Responsive Polymerized Hydrogels. Issue 1 (July 2016) - Jahan, Kazi I.; Goponenko, Alexander; Dzenis, Yuris
Summary: Stimuli‐responsive polymerized hydrogels represent a promising class of materials for biomedical and other applications such as muscle‐type sensors/actuators due to substantial change in dimensions or shape in response to minute change in their environment, resemblance of soft biological tissues, ability to operate in wet environments, and chemical and physical tailorability. However, despite extensive fundamental research, slow response rate and poor mechanical robustness and durability of gels remain the major unresolved barriers for wider application of these materials. Nanostructured responsive polymer gels based on continuous electrospun nanofilaments are expected to have fast response and enhanced strength, modulus, and toughness, thus resolving both main current shortcomings. In this article, poly(vinyl alcohol)–poly(acrylic acid) and Dextran–poly(acrylic acid) pH‐responsive nanofilamentary gels were prepared and compared to bulk gels. In addition to fast response rate, the nanofilamentary gels demonstrated unusual mechanical properties such as cross‐over of load vs. length curves obtained at different pH and anisotropy of response.